PELIBATAN ORANG TUA DALAM PROSES PENDIDIKAN GUNA MENINGKATKAN PRESTASI BELAJAR SISWA - Moh Rifa’i; Sulton Sulton (STKIP Pesisir Selatan, 2026)
The background of this research is rooted in the prevalence of the sociocultural phenomenon of